2023
DOI: 10.1186/s40164-023-00375-5
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of polyfunctional CD26highCD8+ T cells repertoire in chronic lymphocytic leukemia

Abstract: Background CD8+ T cells play an essential role against tumors but the role of human CD8+CD26+ T cell subset against tumors, in particular, haematological cancers such as chronic lymphocytic leukemia (CLL) remains unknown. Although CD4+CD26high T cells are considered for adoptive cancer immunotherapy, the role of CD8+CD26+ T cells is ill-defined. Therefore, further studies are required to better determine the role of CD8+CD26+ T cells in solid tumors and haematological cancers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 103 publications
0
10
1
Order By: Relevance
“…Given the fact that the high expression of CD26 and expression of CD8 is a commonly observed phenotype of MAIT cells and that MAIT cells are predominant in CD8 + CD26 high T-cell subset, the findings presented in this study suggest that MAIT cells are also depleted in the setting of CLL. 28,29 Our study, the first to analyse a broad spectrum of haematological malignancies, implies that the decline of circulating MAIT cells can be considered a general phenomenon in patients with haematological malignancies. Their absolute amount and percentage among the T-cells were decreased when the whole group of haematological patients was compared with the healthy volunteers.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Given the fact that the high expression of CD26 and expression of CD8 is a commonly observed phenotype of MAIT cells and that MAIT cells are predominant in CD8 + CD26 high T-cell subset, the findings presented in this study suggest that MAIT cells are also depleted in the setting of CLL. 28,29 Our study, the first to analyse a broad spectrum of haematological malignancies, implies that the decline of circulating MAIT cells can be considered a general phenomenon in patients with haematological malignancies. Their absolute amount and percentage among the T-cells were decreased when the whole group of haematological patients was compared with the healthy volunteers.…”
Section: Discussionmentioning
confidence: 98%
“…should be considered, as it describes the decrease of circulating CD8 + CD26 high T‐cells in peripheral blood of patients with CLL. Given the fact that the high expression of CD26 and expression of CD8 is a commonly observed phenotype of MAIT cells and that MAIT cells are predominant in CD8 + CD26 high T‐cell subset, the findings presented in this study suggest that MAIT cells are also depleted in the setting of CLL 28,29 …”
Section: Discussionmentioning
confidence: 99%
“…Multiplex analyses of plasma cytokines/chemokines were conducted by Mesoscale Discovery (MSD) kits, as we have reported before [ 45 , 46 ]. Data were obtained on a V‐plex® Sector Imager 2400 plate reader and analyzed on the msd workbench 3.0 software (MSD, Rockville, MD, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, patients with chronic lymphocytic leukemia (CLL) harbored decreased numbers of circulating CD8+CD26hi T cells ( 15 ). It was already shown that MAIT cells express high levels of CD26 ( 13 , 16 ), and the authors confirmed the predominance of MAIT cells within the CD8+CD26hi subset.…”
Section: Mait Cells In Hematologic Malignanciesmentioning
confidence: 99%
“…No study to date has studied MAIT cells exhaustion in the context of hematologic malignancies. However, as already mentioned, MAIT cells are numerically deficient in patients with MM and AML ( 12 , 13 ); the reason for this is still obscure but one possibility would be that MAIT suffer from increased apoptosis ( 15 ). This would represent some kind of immune escape as well.…”
Section: Problems To Overcome Questions To Addressmentioning
confidence: 99%